Perilaku Tumbuh Kantong Semar (Nepenthes mirabilis Druce) di Habitat Alaminya, Taman Nasional Kutai, Kalimantan Timur - Tri Handayani; Inggit Puji Astuti (Fakultas Biologi | Universitas Jenderal Soedirman, 2005)
Nepenthes mirabilis has been widely known as an insectivorous plant species. A study on the growing behaviour of N. mirabilis in Teluk Kaba, Kutai National Park has been carried out. As many as approximately 840 individuals consisting of 307 rosettes and 533 mature plants were found. Variation in tendril’s position was observed in nine rosettes plants and in 22 mature plants. On the other hand, variations in leaf colour appeared in eight individuals. Variations in colour of pitcher and tendril were found in 17 individuals. The natural habitat of N. mirabilis was very specific, and it was also noted that 13 species were assosiated with this plant species. Further result will be discussed in this paper.